Speech therapy for the physically handicapped. - Hawk, Sara Stinchfield, 1885- (Stanford, : Stanford University Press, 1950)
Hoe leer je lichamelijk gehandicapten praten?
Bibliography: p. 233-237.
Keywords: Speech disorders